(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
The main purpose of this scientific article is to fully study and simulate the means of artistic expression of the Uzbek language, which is the object of study, to collect examples from works of art, including Ulugbek Hamdam’s, and to provide cortical and analytical interpretation. In the language of literature, the visual medium is a very ancient and widely used linguistic feature. It reflects the colorful stylistic possibilities of the language. Over time, as the socio-political life is renewed, new nuances appear in the literary language, the visual means acquire a new content, reflect the unique stylistic colors of the language. For this reason, the study of syntactic figures and tropes in the context of the language and style of the writers has always been one of the most pressing and important issues in the field of philology, especially linguistics. That is why linguistics pays great attention to the study of artistic means